Hubungan Penggunaan Gadget Terhadap Potensi Gangguan Pemusatan Perhatian Dan Hiperaktivitas Pada Anak Prasekolah Dipaud Bougenville Cawang - Indah Ika Maya Ningtyas; Dini Nur Alpiah; Slamet Soemarno (JURNAL ILMIAH NUSANTARA, 2024)
This study examines the relationship between gadget use and the potential for Attention Deficit and Hyperactivity Disorders (GPPH) in preschool children. The American Academy of Pediatrics recommends gadget use for preschoolers for no more than 1 hour per day. Gadget addiction can affect a child's brain development because excessive production of the hormone dopamine disrupts the maturity of the prefrontal cortex function, namely controlling emotions, self-control, responsibility, decision making and other moral values. Excessive use of gadgets can also cause problems such as ADHD. The intensity of gadget use was measured using a gadget usage habits questionnaire and GPPH using the Abbreviated Conners Rating Scale (ACRS). This study used a cross-sectional design with 27 respondents in PAUD Bougenville, Cawang with a percentage of 100%, and as many as 29.6% had normal results with a total of 8 children and as many as 70.4% had potential ADHD results with a total of 19 people. Based on the Kendall Tau test, the p-value was 0.005 < 0.05. The results of the correlation test between the gadget intensity variable and the potential for GPPH show that between the variables there is a correlation coefficient (R) of 1,000. This can mean that there is a perfect correlation between the two variables with a strong and significant level of relationship because of the sig value. less than 0.05. It is concluded that there is a significant relationship between gadget use and the risk of attention deficit hyperactivity disorder in preschool children